Effects of peripheral cooling on intention tremor in multiple sclerosis. Issue 3 (16th February 2005) - Feys, P; Helsen, W; Liu, X; Mooren, D; Albrecht, H; Nuttin, B; Ketelaer, P
Abstract : Objective: To investigate the effect of peripheral sustained cooling on intention tremor in patients with multiple sclerosis (MS). MS induced upper limb intention tremor affects many functional activities and is extremely difficult to treat. Materials/Methods: Deep (18°C) and moderate (25°C) cooling interventions were applied for 15 minutes to 23 and 11 tremor arms of patients with MS, respectively. Deep and moderate cooling reduced skin temperature at the elbow by 13.5°C and 7°C, respectively. Evaluations of physiological variables, the finger tapping test, and a wrist step tracking task were performed before and up to 30 minutes after cooling. Results: The heart rate and the central body temperature remained unchanged throughout. Both cooling interventions reduced overall tremor amplitude and frequency proportional to cooling intensity. Tremor reduction persisted during the 30 minute post cooling evaluation period. Nerve conduction velocity was decreased after deep cooling, but this does not fully explain the reduction in tremor amplitude or the effects of moderate cooling. Cooling did not substantially hamper voluntary movement control required for accurate performance of the step tracking task. However, changes in the mechanical properties of muscles may have contributed to the tremor amplitude reduction. Conclusions: Cooling induced tremor reduction is probably caused by a combination of decreased nerve conduction velocity, changed muscle properties, and reduced muscle spindle activity. Tremor reduction is thought to relate to decreased long loop stretch reflexes, because muscle spindle discharge is temperature dependent. These findings are clinically important because applying peripheral cooling might enable patients to perform functional activities more efficiently.